EFFECT OF FENOFIBRATE ADJUVANT THERAPY ON ENDOTHELIAL DYSFUNCTION AND CARDIOVASCULAR RISK IN EGYPTIAN PATIENTS WITH TYPE 2 DIABETES MELLITUS - K HEGAZY, SAHAR; A ELBEDEWY, TAMER; M SAMI, HAIDY (Asian Journal of Pharmaceutical and Clinical Research, 2020)
Objective: Endothelial dysfunction is afflicted to the maturation of arteriosclerosis and type 2 diabetes mellitus (T2DM) vascular complications. This study designed to evaluate the impact of fenofibrate adjuvant therapy on endothelial dysfunction and cardiovascular risk in patients with T2DM. Methods: Seventy-five subjects were recruited from the Internal Medicine Department of Tanta University Hospital. The participants were classified into three groups: Group 1 (control group), 25 healthy subjects; Group 2, 25 T2DM patients received glimepiride/metformin (2:500 mg/day); and Group 3, 25 T2DM patients received glimepiride/metformin (2:500 mg/day)+fenofibrate (300 mg/day). Patients were assessed before and 3 months after intervention for the determination of body mass index (BMI), blood pressure, glycemic picture (hemoglobin A1C % and homeostatic model assessment of insulin resistant), lipid panel, Castelli’s risk index (CRI-I and CRI-II), albumin-to-creatinine ratio (ACR), and endothelial dysfunction biomarkers (asymmetric dimethylarginine [ADMA] and Syndecan-1 (SDC-1)]. Data were statistically analyzed by one-way analysis of variance; p<0.05 was considered statistically significant. Results: The addition of fenofibrate to oral hypoglycemic drugs (Group 3) provoked a significant decrease in all measured parameters when compared with Group 2. As compared to the control group, Group 3 showed no significant difference in most measured parameters after 3 months of therapy. For T2DM patients of Group 3, both ADMA and SDC-1 showed a significant positive correlation with all measured parameters except for high-density lipoprotein cholesterol which exhibited significant negative correlation after 3 months of therapy (p<0.05). Conclusion: The addition of fenofibrate adjuvant therapy to oral hypoglycemic drugs improved the vascular endothelial dysfunction, CRI-I, CRI-II, glycemic picture, lipid panel, ACR, and blood pressure and reduced the BMI in patients with T2DM.